Optimization a new mathematical model of hybrid flow shop work order problem by the Genetic Algorithm - Pour, Nasser Shahsavari; Asadi, Hamed; Kheradmand, Mansoor (International Journal of Engineering and Technology, 2012)
In competitive business, one of the challenges of management in industrial units is reducing the prime cost. Hybrid flow shop is one of the common production environments which lead to a significant decrease in production costs if it has a good and appropriate scheduling in production. Hybrid flow-shop problems overcome one of the limitations of the classical flow-shop model by allowing parallel processors at each stage of task Processing. In this paper we study the hybrid flow shop work order problems. A brief enumeration of the essential constraints that characterize this kind of organization is given. Problem is minimizing the production and inventory cost in Hybrid flow-shop organization. To solve problem we used the genetic algorithm to obtain the minimum of production cost. An illustrative example explains in detail the feature of the proposed model.